Financial-Based Digital Technology Transformation Adapter to Increase the Sustainability of Agribusiness Farmers Sustainable Manner in Indonesia - Gusti, Ratih Andaningsih; Nugrahanti, Trinandari Prasetyo; Susilastuti, Darwati; Yolanda (Ilomata International Journal of Management, 2026)
The importance of financial-based digital technology system transformation in the Agribusiness system to improve the welfare of farmers and entrepreneurs. It is hoped that this digital technology system can be more advanced and sustainable, especially with the Agrofarmers logo, and needs to be implemented sustainably to empower the use of digital technology. The method used in this research is a symmetric descriptive qualitative method with a digital financial information technology system approach that is relevant for farmers and agribusiness entrepreneurs in Indonesia. The contribution of this research is to increase the knowledge and skills of farmers in managing agribusiness by using relevant information technology facilities in their daily business transactions efficiently and effectively. This research is limited to discussing financial-based digital technology transformation to increase the productivity of superior agribusiness farmers in West Java Province in Indonesia in a sustainable manner. The benefits of research for farmers in particular are expected to increase their capacity to use digital technology tools. Financially based and well networked, efficient, effective, good, and correct, so that in the future it is hoped that the productivity of their agricultural products and agribusiness results can increase optimally, maximally, and sustainably. The expected results are that farmers, in particular, and agribusiness entrepreneurs can understand technological transformation.